The Role of Libraries in Building of Islamic Moderation: - - Ayu Yuli Wijayanti; Dawamun Ni'am Alfatawi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2022)
This study aims to reveal efforts to develop Islamic moderation through libraries. Libraries as the center of knowledge management institutions have the potential and reach of the wider community geographically, at various levels. This relates to the types of libraries that tend to have the potential to be easier to accept. Based on this research, it was found that Islamic moderation in the context of the nation and state is a new thing. In fact, it has existed since the early days of Islam, for the Indonesian people, Islamic modernization existed before the era of independence. The development of religious moderation in the library is a very relevant thing to do. The progress of culture and civilization of a nation cannot be separated from the progress of the library. The role of libraries in sowing Islamic modernity is the connection of the present context with history. The discontinuity of history makes a person can be misguided because he does not receive complete information or is trapped in a text without an adequate interpretation of the context. The spread of Islamic moderation needs the right strategy, because it requires a long and continuous step. The strategy is divided into two, namely internal and external. The internal strategy concerns the performance of the library while external is related to support from institutions outside the library which is generally related to the realm of power